KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN SISTEM ENTREPRISE RESOURCE PLANNING (ERP) - Ningtyas, Nova Dia; Khusniyah Indrawati, Nur (Jurnal Management Risiko dan Keuangan, 2022)
The objective of this research is to identify differences in financial performance before and after the application of Enterprise Resource Planning (ERP) at PT. Ekadharma International, Tbk. Here financial performance is measured  based on the aspects of liquidity, leverage, and profitability, proxied by Current Ratio, Debt-to-Asset Ratio (DAR), Debt-to-Equity Ratio (DER), Net Profit Margin (NPM), Return on Assets (ROA), and Gross Profit Margin (GPM). This quantitative research uses secondary data obtained from the company’s financial statements of 2014, 2015, 2016, 2018, 2019, and 2020 published in the Indonesia Stock Exchange and in the company’s website. The Paired Sample T-test performed in IBM SPSS 24 has led to findings that there are differences in financial performance before and after the application of Enterprise Resource Planning system in the aspect of liquidity. However, there is no difference in the said performance before and after the system’s usage in the aspects of leverage and profitability.